Insentif Pajak terhadap Sumbangan Covid-19 dari Perspektif Relasi Hukum Pajak Indonesia dengan Hak Asasi Manusia - Muhammad Syukur (Universitas Negeri Surabaya, 2020)
The Covid-19 pandemic is a transnational threat that requires a global response, but the outbreak has laid bare divergent national approaches to exposed broader structural weaknesses in the governance system. The challenges of governance of the state amidst the Covid-19 pandemic is not only on the public health approach but also must face the risk of economic recession. In the present report, the government of the Republic of Indonesia has taken anticipation steps to prevent and overcome Covid-19 through legislation which is then implemented to the public. The focus of this paper is to review how the Republic of Indonesia maintains national economic resilience using the Indonesian tax law approach. Income tax is part of tax classification in Indonesia has rights and obligations attached to the state as well as taxpayers. With using the doctrinal legal research method, this papers analyzes the perspective of the Republic of Indonesia's tax laws on opportunities for corporate taxpayers to get incentives in their income tax, on the grounds that they have contributed to the need to overcome the pandemic Covid-19 and explained the relationship between human rights and taxes on the case. As the papers make clear, the tax revenue paradigm is considered important because it impacts on economic security and national development. The government must be careful in carrying out taxation policies by considering the economic conditions of democracy, globalization, and the synergy of the center and the regions as long as the Covid-19 pandemic continues. Human rights and taxes are related to the realization of the right to the social-economic and social justice in society because Indonesia taxes has rights and obligations attached to the state as well as taxpayers. Keywords: Covid-19 donations, tax incentive, human rights.